EXPLORING THE BUSINESS MODEL OF A LOCAL INFLUENCER: A QUALITATIVE CASE STUDY OF @SUDUTPAYAKUMBUH USING THE BUSINESS MODEL CANVAS FRAMEWORK - Indika Juang Putra; Rusydi Fauzan (Program Sarjana Manajemen Universitas Internasional Batam, 2026)
This study explores the business model of @sudutpayakumbuh, an Instagram-based creator providing digital branding and creative services in Payakumbuh, West Sumatra. Using the Business Model Canvas framework, the qualitative descriptive research maps out how this digital account operates as a local micro-entrepreneur. The study directly evaluates the core management through in-depth interviews and social media observations. The findings show that the account functions as a creative content studio offering integrated visual production, digital campaigns, and branding strategies. Its primary target audience consists of local Micro, Small, and Medium Enterprises, utilizing a value proposition that combines affordable pricing, professional production quality, and personalized services. Strategic collaborations with creative communities, government bodies, and educational institutions expand its reach and boost local brand visibility. The study concludes that local influencers build sustainable business models by leveraging technology and cultural approaches, playing a vital role in regional creative economy ecosystems.